A probe into the sexual behavior of call center agents. - De Veyra, Djulia M.; Estoya, Kristine Jean B. (Tacloban City Djulia De Veyra, 2011)
It is clear that there are serious medical consequences to risky sexual behaviors. Studies and medical records show that victims of Sexually Transmitted Diseases are increasing at an alarming rate in the call center industry. The consequences can be quite serious. Without question, sexual promiscuity spreads diseases, from trivial to serious to deadly.
The purpose of this study is to assess the degree to which call center agents practice risky sexual behaviors and to see whether they take precautionary actions that would safeguard them from unwanted sexually transmitted diseases.
This study has 112 call center agents as respondents. They comprise 20% of the population. A survey questionnaire was used to acquire the necessary data.
The results of the study show that almost half of the respondents belong to the 'traditional' (45.5%) group. That is, they limit their sexual activities to the conventional ways of doing things. Though this may be good news, it is also imperative to note that just tagging behind the traditional group is the "complacent group" (36.6%). Though this group may not opt to engage in experimental sexual behaviors, this group may be kindled to be so. Lastly, a significant number of these agents do not take precautionary protective measures, like using condoms.
With these results, the researchers conclude that the notion on the prevalence of various health hazards in the call center industry is factual and that the government has to do something about it. Whether such behaviors are a product of the work environment is beyond the scope of this study. Still, there is an obvious need for precautionary initiatives that aim to imbibe an increased awareness of the risks these young professional workers are exposed to.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science